(untitled) (Rome, 2010)
This paper provides practical guidance to aquaculture policy-makers and implementers on policy formulation and processes. It starts by reviewing governance concepts and international policy agendas relevant to aquaculture development and proceeds by defining "policy", "strategy" and "plan" while explaining common planning terminology. The paper proposes practical steps for improving policy formulation processes
Quy hoạch và phát triển nghề cá
Keywords: Aquaculture; Planning